A study on binderless co-pelletization of industrial rice-powder wastes and teak sawdust at low and elevated temperatures - Ronnachart Munsin; Jakkarin Udtasri; Subongkoj Topaiboul; Pichet Kowtakul; Pracha Yeunyongkul; Nawee Nuntapap; Parkpoom Jarupoom; Manop Rakyat; Yossapong Laoonual; Prathan Srichai; Nuttapong Ruttanadech; Thatchapol Chungcharoen (Case Studies in Chemical and Environmental Engineering, 2022)
The objectives of this work were to investigate the effect of rice-powder wastes on binding characteristics of pellet at low temperature (25 °C) and to investigate effect of the elevated temperature of die (80 and 140 °C) on the quality of co-pelletized fuel. Mixing ratios of raw materials, i.e. teak sawdust and rice-powder wastes, were tested at 1:0.5, 1:1, 1:2 and 1:3. The results showed that the mixing ratio of 1:1 was optimal at low temperature for binding considered from a trade-off between the increase in friction versus the increase in density and strength. The qualities of pelletized fuel were improved by the elevated temperatures, especially at 140 °C, resulted in the increase in density, compressive strength and energy density, and the decrease in adhesive friction and moisture content. While the color change of pellet was highly depended on die temperature (10 at 80 °C and over 15 at 140 °C), the color change of pellet was not dominated by type of rice-powder wastes.
Keywords: Natural Fiber Reinforced Composites; Thermochemical Biomass Conversion Processes; Recycling and utilization of industrial and municipal waste in materials production